Plastic made gasing top - Sulaiman, Shamsuddin; Baharudin, B. T. Hang Tuah; Mohd Ariffin, Mohd Khairol Anuar; Rozali, Mohd Jais (2012)
A gasing top comprises a plastic or plastic composite body; a metal rod positioned within the body and extending along the central axis of the body towards the bottom forming a sharp tip, which is located outside the body to serve as a spinning tip; and a weight located within the body being arranged in such a way to stabilize spinning of the gasing top.